Association between environmental composite quality index score and obesity in children and their family: A cross-sectional study in northeast China. (June 2022) - Liang, Hong; Zhang, Yixin; Zhang, Shen; He, Yu; Gao, Jie; Wang, Lining; Wang, Yuhan; Hang, Dong; Ma, Yanan
Abstract: Background: Childhood obesity has emerged as a severe public health problem worldwide. Most studies focused on the association between single environmental risk factors and obesity. Thus, we investigate the association between environmental composite quality index (ECQI) score and obesity in children and their families. Method: The cross-sectional study was conducted among 2354 children and 1761 mothers in Fuxin City, Liaoning Province, in 2015. The information was collected by questionnaires, including environmental factors, heights, weights, and sociodemographic data. We quantitated thirteen indoor and outdoor risk factors and constructed the ECQI. There were 4 household environmental factors in the household air quality index (HAQI) and 9 variables to evaluate the outdoor environmental quality index (OEQI). Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using the binary logistic regression model after adjusting the most common obesity risk factors. Results: A higher ECQI score was correlated with a higher risk of childhood obesity and family obesity. Comparing the ECQI score 0–2 to the ECQI score ≥5, ORs with childhood obesity was 1.73 (95%CI, 1.25–2.39, P for trend = 0.001), and 1.53 for family obesity (95%CI, 1.09–2.15; P for trend = 0.003) after adjusted confounding factors. Similarly, a significantly positive association was found between OEQI score, HAQI score, and childhood obesity, family obesity. Conclusion: A higher ECQI score was associated with an increased risk of obesity in children and their families. Both HAQI score and OEQI score were associated to childhood obesity and family obesity. Further studies should elucidate the underlying mechanisms. Graphical abstract: Image 1 Highlights: The study pays attention to the environmental composite quality index (ECQI). The ECQI score is positively associated with childhood obesity. There is a significant association of ECQI scores with family obesity.